The Technological Disaggregation as a Tool for the Generation of Public Policies to Encourage Innovation - Naranjo Silva, Héctor Sebastián (2018)
The article analyses the potential that the technological disaggregation has for the generation of public policies that encourage innovation, as a technical tool for the assimilation of technology. Mechanisms that the countries of the region use to promote innovation and that allow the development of products in order to move from an extractive economy to one focused on innovative services are considered. The main problem found at the regional level is the lack of regulations and excessive bureaucracy that do not promote innovative and technological environments.